ACCOUNTING DISCLOSURE OF SOCIAL RESPONSIBILITY AND ITS IMPACT ON THE DIMENSIONS OF SUSTAINABLE DEVELOPMENT - Mahdi Abbas Abadi (Scholars Digest Publishing, 2024)
The research aims to demonstrate accounting disclosure of social responsibility and its impact on the dimensions of sustainable development, by identifying the theoretical aspects of accounting disclosure, social responsibility and dimensions of sustainable development. The importance of the research stems from identifying the role of accounting disclosure of social responsibility in enhancing the organization's reputation and increasing the brand. It clarifies that environmental considerations and sustainability are an integral part of the company's values and operations. The research problem can be reviewed through the following question: "How does accounting disclosure of organizations' social responsibility practices affect the dimensions of sustainable development?" The research hypothesis was formulated about the impact of accounting disclosure of social responsibility on the economic, social and environmental dimensions of sustainable development. In order to achieve the goals sought by the research, the researcher prepared a questionnaire to clarify the opinions of employees at Baghdad Soft Drinks Company in determining the impact of accounting disclosure of social responsibility on the economic, social and environmental dimensions of sustainable development. One of the most important results reached by the research is the great importance of accounting disclosure of social responsibility on the economic, social and environmental dimensions of sustainable development by attracting socially conscious investors who They prioritize sustainability as it gives organizations a competitive advantage in the market, enhances transparency and accountability, enables organizations to provide data and evidence about their social initiatives, and encourages engagement with stakeholders so that they become more aware of environmental issues related to organizations.
Keywords: accounting disclosure, social responsibility, dimensions of sustainable development